PENINGKATAN PENDIDIKAN KESIAPSIAGAAN BENCANA SEKOLAH DASAR BENGKULU MELALUI PEMBELAJARAN TEMATIK TERPADU DAN MEDIA ICT - Endang Widi Winarni; Feri Noperman; Endina Putri Purwandari (DHARMA RAFLESIA, 2018)
The aims of this dedication activity were: (1) prepared human resources, infrastructures, and learning model about disaster preparedness; (2) disseminated learning model of disaster preparedness through integrative thematic learning; (3) disseminated learning model of disaster preparedness through ICT media. This activity used observational and modelling method with four phases, i.e., attentional phase, retension phase, reproduction phase, and motivation phase. The result of this activity indicated that all teacher (100%) have true perception and comprehension about disaster risk reduction program. Besides, this activity produced of learning plan and online learning resource about disaster risk reduction program. The online learning resource can be accessed by www.wartabencana.com. Keywords: learning model of disaster preparedness, the reduction of disaster risk program